PEMBIAKAN STOMOXYS CALCITRANS (DIPTERA .: MUSCIDAE) DI LABORATORIUM - ENDANG PURWANINGSIH; IYOK BUDIARTI (BERITA BIOLOGI, 1986)
E. PURWANINGSIH & I. BUDIARTI. 1986. Rearing Stomoxys calcitrans (Diptera : Muscidae) in the laboratory. Berita Biologi 3(5): 240 - 243. The stable fly 5. calcitrans was reared in the laboratory in an attempt to the study the biology. Flies captured from the field were used as parent stock. Eggs were laid within 4 days after captured. The total number of eggs deposited were 48 (15-96) with an incubation period of 1,6 (1-3) days. The larval and pupal period were 4,9 (8-23) days and 6,4 (1-3) days respectively. Hatching of eggs reach 26,1 (21,4-31,1) %. Adult emergence reach 86 %. Feeding activities was recorded for the adult as well as larvae. Flies could survive for 2-32 days in the laboratory without any sign of being able to produce offspring. Behaviour and the morphology of each development stage were discussed.